2020
DOI: 10.3390/cancers12051177
|View full text |Cite
|
Sign up to set email alerts
|

On-Treatment Changes in FIB-4 and 1-Year FIB-4 Values Help Identify Patients with Chronic Hepatitis B Receiving Entecavir Therapy Who Have the Lowest Risk of Hepatocellular Carcinoma

Abstract: Noninvasive fibrosis indices can help stratify the risk of hepatocellular carcinoma (HCC) in patients with chronic hepatitis B (CHB) receiving nucleos(t)ide analogue (NA) therapy. We investigated the predictive performance of on-treatment changes in FIB-4 (△FIB-4) and 1-year FIB-4 values (FIB-4 12M) for HCC risk in patients with CHB receiving entecavir therapy. We included 1325 NA-naïve patients with CHB treated with entecavir, retrospectively, from January 2007 to August 2012. A combination of △FIB-4 and FIB-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Although ALT normalization did not significantly affect HCC occurrence (HR 0.771; p = 0.339) in the current study, multivariate analysis showed that FIB‐4 reduction after 1 year of ETV therapy was strongly associated with HCC incidence (HR 0.491; p = 0.013) (Table 4). In addition, a previous study 17 showed on‐treatment change in the FIB‐4 index helped to identify patients with CHB who have the lowest risk of HCC, as we suggested in the current study. The authors of the previous study suggest an algorithm for HCC prediction in CHB patients treated with ETV according to cut‐off value of 12 months (noncirrhosis 1.58 vs. cirrhosis 2.88) and the presence of on‐treatment FIB‐4 index after 1 year of ETV therapy.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Although ALT normalization did not significantly affect HCC occurrence (HR 0.771; p = 0.339) in the current study, multivariate analysis showed that FIB‐4 reduction after 1 year of ETV therapy was strongly associated with HCC incidence (HR 0.491; p = 0.013) (Table 4). In addition, a previous study 17 showed on‐treatment change in the FIB‐4 index helped to identify patients with CHB who have the lowest risk of HCC, as we suggested in the current study. The authors of the previous study suggest an algorithm for HCC prediction in CHB patients treated with ETV according to cut‐off value of 12 months (noncirrhosis 1.58 vs. cirrhosis 2.88) and the presence of on‐treatment FIB‐4 index after 1 year of ETV therapy.…”
Section: Discussionsupporting
confidence: 53%
“…Another study of 539 patients with nucleoside/nucleotide therapy reported that a FIB‐4 index of more than 2.65 had predictive power for HCC incidence 13 . In addition, recently, Wang et al 17 . suggested a predictive algorithm for HCC risk estimation using a specific value of FIB‐4 index and on‐treatment change in the FIB‐4 index after 1 year of ETV treatment for CHB patients with or without LC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the present study was conducted solely based on a retrospective, single-center cohort in a large tertiary referral university hospital, and its results are potentially subject to selection bias. Second, although we validated the predictive performance of the initial aMAP score and the 1-year aMAP score, the predictive role of the combination of aMAP and on-treatment changes in aMAP (ΔaMAP) during NA therapy and their optimal time point requires further investigation, as in the case of the fibrosis index based on four factors (FIB-4) ( 32 ). Third, given that metabolic risk factors, including diabetes, obesity, high blood pressure, and hypercholesterolemia, are associated with an increased HCC risk in patients with CHB ( 33 ), other metabolic risk factors should be incorporated in future studies as such models will have higher discriminatory power.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed determinants of liver-related events; however, the reported predictors have not been consistent. 14 , 16 , 27 In this retrospective study, we determined independent risk predictors for liver-related events, liver-related mortality, and HCC from widely validated models developed with routinely available laboratory parameters.…”
Section: Discussionmentioning
confidence: 99%